ENDOVASCULAR TREATMENT FOR CRITICAL ISCHEMIA OF THE LOWER EXTREMITIES IN PATIENTS WITH DIABETIC FOOT SINROME - Наимов Фариджон Фахриддинович (Journals Park Publishing, 2023)
According to the calculations of our researchers, occlusive diseases of the arteries of the lower extremities affect from 3 to 10% of the population, increasing to 15-20% among patients older than 70 years [1,3]. In a third of patients with critical ischemiaof the lower extremities, 6-8 years after the appearance of the first signs of the disease, critical ischemia develops. According to some epidemiological studies, the incidence of peripheral artery disease in patients with diabetes is from 10 to 40%, and in the presence of ulcerative foot defects it reaches 50% [4,5]. In Uzbekistan, chronic ischemia of the lower extremities was diagnosedin more than a hundred thousand people. Vascular atherosclerosis is the cause of chronic ischemia of the lower extremities in 80-90% of cases. Especially often this pathology is observed in people over 60 years of age [2].